2015
DOI: 10.1007/s10484-015-9289-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient Adverse Side Effects During Neurofeedback Training: A Randomized, Sham-Controlled, Double Blind Study

Abstract: The benefits of clinical neurofeedback training are well known, however, its adverse side-effects are less studied. This research focuses on the transient adverse side effects of neurofeedback training via a double-blind, sham/controlled methodology. Thirty healthy undergraduate students volunteers were randomly divided into three treatment groups: increasing a modified Sensory Motor Rhythm, increasing Upper Alpha, and Sham/control group who receive a random reward. The training sessions were administered for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…Using active placebo procedures have far less damaging side effects compared to many pharmaceutical interventions. Furthermore, bio/neurofeedback procedures are built on operant conditioning principles, which facilitate active learning techniques that have few, short-lived side effects compared to many long-lived pharmaceutical side effects (Luctkar-Flude, Groll, & Tyerman, 2017;Rogel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Using active placebo procedures have far less damaging side effects compared to many pharmaceutical interventions. Furthermore, bio/neurofeedback procedures are built on operant conditioning principles, which facilitate active learning techniques that have few, short-lived side effects compared to many long-lived pharmaceutical side effects (Luctkar-Flude, Groll, & Tyerman, 2017;Rogel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The participant will report the worsening of side effects compared to the status prior to the first session. They will report "1" if the side effect worsened or a "0" if there is no change in the symptom (Rogel et al, 2015). All the participants will be asked, "Which condition do you think you received?''…”
Section: Primary Outcomesmentioning
confidence: 99%
“…In a study of 30 young healthy adults, 70% reported 78 side effects. Most were mild and transient, for example, headaches, fatigue, and mood swings (Rogel et al, 2015). Adverse side effects can be divided into nonspecific, associated with the training in general, and specific, associated with the particular protocol (Matthews, 2007;Ochs, 2007;Rogel et al, 2015).…”
Section: The Effects Of Side Effectsmentioning
confidence: 99%
“…Most were mild and transient, for example, headaches, fatigue, and mood swings (Rogel et al, 2015). Adverse side effects can be divided into nonspecific, associated with the training in general, and specific, associated with the particular protocol (Matthews, 2007;Ochs, 2007;Rogel et al, 2015). Applying inappropriate NFT protocols has been found to be a major cause while certain protocols are more likely to cause specific side effects, for example, increasing power (Hammond & Kirk, 2008;Lubar et al, 1981;Whitsett, Lubar, Holder, Pamplin, & Shabsin, 1982).…”
Section: The Effects Of Side Effectsmentioning
confidence: 99%